TRADISI PRASAH DI SIDIGEDE WELAHAN JEPARA DALAM PERSPEKTIF ‘URF - Nur Naila Izza (Faculty of Sharia and Law UNISNU Jepara, 2020)
the Prasah tradition in marriage in Sidigede Village, Welahan District, Jepara Regency and to understand the implementation of the Prasah tradition in the 'urf review in Sidigede Village, Welahan District, Jepara Regency. This research uses a normative-sociological approach, qualitative research and deductive analysis methods. The data collection methods used were interviews, observation, and documentation. The results of this study state that, first, the Prasah tradition in Sidigede Village, Welahan District, Jepara Regency which is preserved as a tradition that leads to a gift of a buffalo to the prospective bride. The word prasah comes from the Javanese resigned language which means surrendered, approved. To make it easier to pronounce, the word surrender is changed to prasah. However, over time there was a difference of opinion among the people of Sidigede Village who said that prasah was a dowry and an ordinary gift. Second, the prasah tradition is an utterance or agreement and is not contained in the Qur'an, sunnah, ijmak, and qiyas, so the researcher categorizes that prasah is included in the 'urf category, namely al-'urf al-sahih. Prasah is also included in the category of al-'urf al-'amali because prasah is a habit in the form of actions carried out by the people of Sidigede Village. And prasah is also categorized into al-'urf al-khas because prasah is devoted to the people of Sidigede Village, Welahan District, Jepara Regency. Penelitian ini bertujuan untuk meneliti tentang tradisi Prasah dalam perkawinan di desa Sidigede Kecamatan Welahan Kabupaten Jepara dan untuk memahami pelaksanaan tradisi Prasah dalam tinjauan ‘urf di Desa Sidigede Kecamatan Welahan Kabupaten Jepara. Penelitian ini menggunakan pendekatan normatif- sosiologis, jenis penelitian kualitatif dan metode analisis deduktif. Metode pengumpulan data yang digunakan wawancara, observasi, dan dokumentasi. Hasil penelitian ini menyatakan bahwa, pertama, tradisi Prasah di Desa Sidigede Kecamatan Welahan Kabupaten Jepara yang dilestarikan sebagai suatu tradisi yang mengarah pada suatu pemberian seekor kerbau kepada calon mempelai wanita. Kata prasah berasal dari bahasa jawa pasrah yang artinya diserahkan, disahkan. Supaya lebih mudah dilafalkan maka kata pasrah diubah menjadi prasah. Namun, seiring berjalanya waktu terjadi perbedaan pendapat masyarakat Desa Sidigede yang mengatakan bahwa prasah merupakan sebuah mahar dan pemberian biasa. Kedua, tradisi prasah merupakan suatu ucapan atau kesepakatan dan tidak ada